Diseño y construcción de un prototipo de potenciostato galvanostato para el laboratorio de corrosión de la escuela de ingeniería metalúrgica (2004)
The current circumstances motivate the University as an axis of regional development, to propose alternatives that enable it to develop dynamically and as a manager of its own evolution. It is thus making a first attempt to implement policies of import substitution and strategies to minimize the cost of equipment, (E3T) and of Metallurgical Engineering and Materials Science (EIMCM), are currently developing a project for the construction of UIS equipment, which will allow the completion of laboratory activities and that can be reviewed and repaired on the spot. The present article explains the process followed for the design and construction of a first prototype to be implemented in the corrosion laboratory of the EIMCM, which has been called the Galvanostat Autonomous Power System (SPGA). An Autonomous Galvanostat Potentiostat System is defined as an equipment that allows to perform electrochemical tests for purposes of assessing corrosion in a material; either by supplying a controlled potential difference and by sensing the current flowing through an electrochemical cell (Potentiostat mode) or by supplying a controlled current by sensing the potential difference at the terminals of the cell (Galvanostat mode), automatically recording the values ​​at length of the test, indicating abnormal situations and deactivating the equipment when the conditions so require, also offering the possibility of transmitting the data to a pey and generating the visualization of the data to allow observations and conclusions about the test.